2017
DOI: 10.1016/j.jiph.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of Saudi populations regarding seasonal influenza vaccination

Abstract: The World Health Organization Global Vaccine Action Plan aims to accelerate the control of preventable diseases, including seasonal influenza; however, seasonal influenza vaccination reluctance persists. The current study aimed to assess the knowledge and attitudes of Saudi nationals regarding seasonal influenza vaccinations. An anonymous questionnaire was targeted to Saudi nationals for self-enrolment in this study. Data were analyzed using descriptive and chi-squared analyses. This study included 1298 Saudi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 12 publications
8
43
1
Order By: Relevance
“…These findings were in accordance with those on adulthood in the same geographical area, in which only 35.4% knew that vaccination against influenza is recommended for patients with chronic diseases [9]. A lower level was found in the US [28], where only 19.6% of adults aged ≥18 years were knowledgeable, whereas higher levels, although in different populations, were found in France [29] and Saudi Arabia [30] where 39% and 36.7%, respectively, knew that people with chronic diseases should receive a vaccine, and in Turkey where almost half of the hospitalized participants stated that pneumococcal vaccination was necessary [31]. The low level of knowledge is worrying because it could be a barrier to the demand for preventive measures that can improve the health status of patients with chronic diseases.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were in accordance with those on adulthood in the same geographical area, in which only 35.4% knew that vaccination against influenza is recommended for patients with chronic diseases [9]. A lower level was found in the US [28], where only 19.6% of adults aged ≥18 years were knowledgeable, whereas higher levels, although in different populations, were found in France [29] and Saudi Arabia [30] where 39% and 36.7%, respectively, knew that people with chronic diseases should receive a vaccine, and in Turkey where almost half of the hospitalized participants stated that pneumococcal vaccination was necessary [31]. The low level of knowledge is worrying because it could be a barrier to the demand for preventive measures that can improve the health status of patients with chronic diseases.…”
Section: Discussionsupporting
confidence: 87%
“…116 In general, a small proportion of pilgrims do not want to be vaccinated owing to misconceptions regarding immunization, such as vaccines weakening the immune system and not being safe. 117 There has also been evidence of certain Muslim communities refusing vaccination on religious grounds; 118 although, the Islamic faith generally recognizes vaccination as a means to protect life. 119…”
Section: The Hajjmentioning
confidence: 99%
“…A recently published review [10] demonstrated that vaccine acceptance and hesitancy vary at the global context. In Saudi Arabia, a COVID-19 vaccine is expected to face signi cant public hesitancy given the current public hesitancy toward seasonal in uenza vaccination [11,12]. Thus, the study aimed to assess the beliefs of Saudi Arabians toward eventual COVID-19 vaccination and to uncover the barriers associated with vaccination among the general population in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%